Series Connected Multilevel Inverter Modules for Grid Tied PV Application - V Jayakumar, V Vengatesh, S Naveenkumar, S Neerajkumar, M Prabhu (International Journal of Advanced Science and Technology, 2020)
In a day to day life electricity demand rapidly increasing and the decreasing of fossil fuel sources, most of the countries around the world goes to renewable energy such as wind energy and solar energy(PV generation). Among other sources of generation Photovoltaic Generation has caught wide spread attention. It is important to use Multilevel Inverters in PV grid applications to get optimal performance from the system. They help greatly in reducing the Total Harmonic Distortion (THD). A multilevel inverter module with a pair of Photovoltaic Modules is proposed in this project